Know my name : a memoir - Miller, Chanel (2019)
Brock Turner had been sentenced to just six months in county jail after he was found sexually assaulting "Emily Doe" on Stanford's campus. Her victim impact statement was posted on BuzzFeed, where it instantly went viral, was translated globally, and read on the floor of Congress. It inspired changes in California law and the recall of the judge in the case. Now Miller reclaims her identity to tell her story of trauma, transcendence, and the power of words. She tells of her struggles with isolation and shame during the aftermath and the trial, reveals the oppression victims face in even the best-case scenarios, and illuminates a culture biased to protect perpetrators. --
Keywords: Miller, Chanel; Rape victims -- United States -- Biography; Women -- Crimes against -- California -- Stanford -- Case studies; Rape -- California -- Stanford -- Case studies; Rape in universities and colleges -- California -- Stanford -- Case studies; Judicial error -- California -- Case studies; Trials (Rape) -- California -- Case studies; Sex discrimination in justice administration -- California -- Case studies; Rape in universities and colleges; Rape victims; Women -- Crimes against; United States; Autobiographies; Autobiographies; Biography; Autobiographies; True crime stories